Impact of Rainfall Patterns, Chemical and Biochemical Transformation in Agricultural and Environmental Systems - Anggraini, Welly; Manaasika, Zidny; Wiliyanti, Vandan (Jurnal Pijar Mipa, 2025)
Climate change driven by rising air temperature and humidity significantly impacts agricultural ecosystems' rainfall patterns and chemical and biochemical processes. This study aims to analyze the relationship between temperature, air humidity, and rainfall and their effects on chemical and biochemical transformations in agricultural and environmental systems in Lampung. This research employs a descriptive quantitative and qualitative approach. Primary data were collected through field observations, soil chemical testing, and public health surveys. Secondary data regarding temperature, humidity, and rainfall were obtained from BMKG. Surveys were conducted using structured questionnaires with purposive sampling techniques targeting affected communities. Data were analyzed using descriptive statistics and linear regression to examine relationships between variables, while chemical analysis measured changes in pH, nutrients, and greenhouse gas emissions. Data processing was performed using SPSS and Excel, and triangulation was conducted to ensure accuracy. The findings indicate that increases in temperature and humidity correlate with a 15% rise in annual rainfall over the last decade. The primary observed effects include increased soil acidity (pH decrease by 0.5-1.0 units), a nitrogen level reduction of up to 20%, and increased greenhouse gas emissions such as CH4 and CO2. Additionally, higher rainfall contributes to increased soil erosion and water pollution. In the health sector, surveys indicate a rise in waterborne diseases (diarrhea, cholera) and respiratory disorders. In conclusion, changes in temperature and humidity have complex effects on agriculture, the environment, and public health, necessitating adaptation and mitigation strategies to reduce their negative impacts.